Women parenting together : motherhood and family life in same sex relationships - Almack, Kathryn (2002)
This study is based on joint and separate in-depth interviews with twenty (female) same sex couples who planned and had their children together in the context of their relationship. These families are one example of the increasing possibilities to live in non-traditional relationships and family forms, in contemporary Western societies. While lesbian and gay parents have a long history, there is little precedence for same sex couples setting up families 'from scratch' i.e. choosing to have children in the context of their relationship. These possibilities can be placed in the context of wider transformations of intimacy.